2019
DOI: 10.9734/jaeri/2019/v18i330061
|View full text |Cite
|
Sign up to set email alerts
|

Income Diversification and Sustainable Land Management Practices among Rural Cassava-based Farmers in Imo State

Abstract: Aims: To examine the income diversification activities and sustainable land management practices among rural cassava-based farmers in Imo State, Nigeria. Study Design: Primary data collection. Place and Duration of Study: Michael Okpara University of Agriculture, Umudike, Pre-requisite study, Post-Graduation in Agricultural Resource and Environmental Economics, between August 2017 and January 2018. Methodology: Data were collected using well-structured questionnaire, administered to rural cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 39 publications
2
2
0
Order By: Relevance
“…Similarly, Chhabra et al (2018) observed that agroforestry is one of the best options that increases resilience to farmers because it reduces pressure on forests by increasing tree cover; and mitigates climate change effects because the amount of carbon stored in the soil system depends on agricultural management systems and practices. Similar findings were reported by Eririogu et al (2019): that cassava-based farmers in Imo State, Nigeria, adapted agroforestry to ensure food security throughout the year. Further, a similar observation reported that agroforestry protect crops from extreme climatic events, such as strong winds, protects crops from lower precipitation as they maintain moisture in a place (Sileshi et al, 2012).…”
Section: Land-use Management Practices and Adaptation To Climate Vari...supporting
confidence: 85%
See 1 more Smart Citation
“…Similarly, Chhabra et al (2018) observed that agroforestry is one of the best options that increases resilience to farmers because it reduces pressure on forests by increasing tree cover; and mitigates climate change effects because the amount of carbon stored in the soil system depends on agricultural management systems and practices. Similar findings were reported by Eririogu et al (2019): that cassava-based farmers in Imo State, Nigeria, adapted agroforestry to ensure food security throughout the year. Further, a similar observation reported that agroforestry protect crops from extreme climatic events, such as strong winds, protects crops from lower precipitation as they maintain moisture in a place (Sileshi et al, 2012).…”
Section: Land-use Management Practices and Adaptation To Climate Vari...supporting
confidence: 85%
“…Also, Heyi and Mberengwa (2012) pointed out that weed management by herbicides enhance soil organic matter through reduced or zero tillage. Moreover, Eririogu et al (2019) show that, in Nigeria, cassava was grown successfully under no-till to give it optimum growth, while conserving the soil's physical properties. Also, it was revealed through FGDs and KIIs that farmers applied mulching and crop residue management to improve soil fertility.…”
Section: Land-use Management Practices and Adaptation To Climate Vari...mentioning
confidence: 99%
“…Similarly, Chhabra et al (2018) observed that agroforestry is one of the best options that increases resilience to farmers because it reduces pressure on forests by increasing tree cover; and mitigates climate change effects because the amount of carbon stored in the soil system depends on agricultural management systems and practices. Similar findings were reported by Eririogu et al (2019): that cassava-based farmers in Imo State, Nigeria, adapted agroforestry to ensure food security throughout the year. Further, a similar observation reported that agroforestry protect crops from extreme climatic events, such as strong winds, protects crops from lower precipitation as they maintain moisture in a place (Sileshi et al, 2012).…”
Section: Land-use Management Practices and Adaptation To Climate Vari...supporting
confidence: 85%
“…Also, Heyi and Mberengwa (2012) pointed out that weed management by herbicides enhance soil organic matter through reduced or zero tillage. Moreover, Eririogu et al (2019) show that, in Nigeria, cassava was grown successfully under no-till to give it optimum growth, while conserving the soil's physical properties. Also, it was revealed through FGDs and KIIs that farmers applied mulching and crop residue management to improve soil fertility.…”
Section: Land-use Management Practices and Adaptation To Climate Vari...mentioning
confidence: 99%